Effects of Ivermectin on packed cell volume of goats when used to treat lice infestation - Maule, J.P. (1990)
The book describes most of the breeds of cattle, over 300 in the tropics. It sets out a simple classification of the main types, zebu, Sanga, humpless and crosses between them and gives a short description of each. This is followed by an account of development of some of the tropically adapted breeds and the success and limitations of some of them. There is lack of accurate information on the performance and ability of indigenous breeds to respond to better management. The book emphasises the need for proper evaluation of potentially useful breeds and describes some projects that give detailed comparisons of promising beef breeds in southern Africa. The author emphasises on the potential value of a number of indigenous breeds not fully appreciated; ways of improving production and breeding efficiency.